The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/23311932.2021.1921950
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of smallholder commercialization of livestock: A case study from Tigray, Ethiopia

Abstract: In several developing countries, including Ethiopia, the change from a subsistence-oriented production system to a market-oriented production system as a means of raising smallholder incomes and mitigating growing rural deprivation has been at the center of the agenda. Therefore, the purpose of this analysis was to evaluate the determinants of smallholder livestock commercialization in Tigray, Ethiopia. One hundred and eighty-three households were selected using a simple random sampling technique. The data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The Heckman two-stage model is reasonable here for this significant lamda. The result is similar to [80,81].…”
Section: Heckman Analysissupporting
confidence: 75%
See 1 more Smart Citation
“…The Heckman two-stage model is reasonable here for this significant lamda. The result is similar to [80,81].…”
Section: Heckman Analysissupporting
confidence: 75%
“…The positive relation revealed that education strengthened the capacity of beef cattle relevant development and marketing knowledge, which boosts profit maximisation from beef cattle. Studies [81,91] found the same positive relationship between commercialization and education.…”
Section: Heckman Selection Modelmentioning
confidence: 67%
“…In Kenya, youth, relative to nonyouth, were found to be concentrated in agricultural production and to have lower access to services (Maina and Maina, 2012). The education level of the household head, access to extension agents, and the total livestock and land owned significantly affected commercialization in Ethiopia (Belay et al, 2021). Girma and Abebaw (2012) similarly found that education and access to extension were important, in addition to market information, adoption of modern livestock inputs, volume of sales, and time spent to reach the market significantly influence participation in the livestock market and his/her choice of a market channel.…”
Section: Conceptual Approachmentioning
confidence: 99%
“…Some strategies have been adopted to overcome the problem of food shortage in developing countries, such strategies include adoption of drought resistance food crops such as cassava and the use of modern agricultural technologies such as improved seeds, use of fertilizers, pesticides, proper spacing and agricultural mechanization is imperative. Similarly, the growing food demand and livestock production resulted from population increase in the urban areas in SSA offers high chances for smallholder farmers to profitably raise cassava production and improve their livelihood (Belay et al, 2021;Ochieng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%